PEMODELAN PENGOLAHAN LIMBAH KERAJINAN JUMPUTAN PALEMBANG BERBASIS “GREEN SUPPLY CHAIN NETWORK” - Bunga Intan; Diana Diana; M. Izman Herdiansyah (Jurnal Bina Komputer, 2019)
The role of Green Suply Chain to a company or small and medium industries (IKM) such as the jump industry for environmental sustainability is very important especially in waste processing. One way that can be done is to make a model starting from raw materials obtained then processed to flow again to the user for the formation of an effective process flow called the process of Green Supply Chain Management. Model of Green Supply Chain Mangement waste processing industry waste cloth industry into clean water other than that with the model of Green Supply Chain Mangement can help the government in reducing the environmental damage caused by waste from the industrial waste jumputan. In this paper the research is in the area of ​​craftsmen Mr Palembang Potato. We analyze and develop a model to improve performance in waste disposal processing in the jump industry industry with the main objective of optimizing or minimizing total cost in waste disposal processing